Repeated Evaluations of Testes and Semen Characteristics in Two Binturongs (Arctictis binturong) - Zainuddin, Zainal Zahari; Sipangkui, Symphorosa; Farqhan Kelana, Mohd; Chee, Yap Keng; Tarmizi, Mohamed Reza Mohamed; Comizzoli, Pierre (Frontiers in Veterinary Science, 2021)
The binturong is a medium size carnivore belonging to the Viverrid family that lives in dense forests of South-East Asia. In addition to the protection of this vulnerable species in its natural habitat (in situ), conservation breeding efforts (ex situ) aim at maintaining a good genetic diversity while increasing the number of individuals to reinforce wild populations. Both approaches require a solid understanding of binturong’s basic biology. However, there is still a lack of precise information about reproduction. The objective of this brief research report was to analyze testicular sizes and semen characteristics at different times of the year. A secondary objective was to describe sperm cryotolerance for the first time in that species. Examinations of testes and semen collections were conducted on two adult males. While testicular measurements were relatively constant across multiple examinations, semen characteristics (volume, viability, sperm concentrations, sperm motility) varied between samples. However, incidence of sperm morphological abnormalities was consistently high. Sperm cryotolerance appeared to be poor but further studies are warranted. The present dataset will be useful for future research on binturong reproduction and for the development of assisted reproductive techniques and biobanking of germplasms.